(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A multiple-input-multiple-output lightweight printed ultrawideband antenna among a dimension about 40×50mm2to minimise the coupling between these two antennas, the proposed antenna with a quarter circular radiating patch, with defected ground structure is designed. The antenna developed by MIMO is highly isolated, stronger than -15dB. In the working band, from 2.67GHz to 14GHz. The simulation indicates that the proposed MIMO antenna will balance the complete enhanced band with a broad bandwidth by making use of CST. It operates at 5.83GHz, 8.07GHz, 12.28GHz and bandwidth tends to cover the ultrawideband range. UWB band and high isolation, that assemblesit perfect for any application of wireless modules in the UWB range, in order to minimise coupling. For indoor applications and wireless applications these frequency range is used.